BOLIVARIAN FOREIGN POLICY: VENEZUELA´S INTERNATIONAL INSERTION DURING HUGO CHÁVEZ FRÍAS FIRST-TWO MANDATES (1999-2007) - de Moraes Cicero, Pedro Henrique (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The article investigates, in three stages, the Venezuelan foreign policy exercised between 1999 and 2007. Initially, efforts were made to strengthen OPEC. Yet, between 2001 and 2003, the internal political crisis had a negative impact on the international insertion sought by the Venezuelans. Finally, between 2004 and 2007, the initial proactive approach was taken based on “diplomacy of oil.”